Oxidative stress protection and growth promotion activity of Pseudomonas mercuritolerans sp. nov., in forage plants under mercury abiotic stress conditions - Robas Mora, Marina; Fernández Pastrana, Vanesa M.; González Reguero, Daniel; Gutiérrez Oliva, Laura L.; Probanza Lobo, Agustín; Jiménez Gómez, Pedro A. (Frontiers in Microbiology, 2022)
Strain SAICEUPSMT was isolated from soils of Almadén (Ciudad Real, Spain), subjected to a high mercury concentration. The ability of this strain to improve plant fitness was tested on lupine model, demonstrating a great potential for plant phytoprotection against mercury stress. Strain SAICEUPSMT significantly increased total plant weight, root weight and number of leaves under mercury stress. When the mercury content of the plant with and without bacterial inoculum was analyzed, it was found that the incorporation of the SAICEUPSMT strain sig-nificantly reduced the absorption of mercury by the plant, while favoring its development in terms of biomass. Additionally, root inoculation with SAICEUPSMT strain under mercury stress produces a significant reduction in the enzymatic response to oxidative stress (catalase, CAT; ascorbate peroxidase, APX; and superoxide dis-mutase, SOD). It can be considered that the strain exerts a phytoprotective effect on the plant. The identification of the strain as a new taxon not described to date is based on both, phenotypical and genotypical identification. The 16S rRNA gene sequence classified the strain as Pseudomonas iranensis. However, whole genome analysis showed that average nucleotides identity (ANI, 95. 47%), DNA-DNA hybridization in silico (dDDH, 61.9%), average amino acids identity (AAI, 97.13%), TETRA (0.99%), and intergenic distance (0.04) values were below the thresholds established for differentiation. This strain was able to produce siderophores, auxins and deaminate stress precursors in vitro. The most represented fatty acids were C16:0 (33.29%), aggregate characteristic 3 (22.80%) comprising C16:1 ω7c and C16:1ω6c, aggregate characteristic 8 (13.66%) comprising C 18:1 ω7 c, and C 18:1 ω6 c and C 17:0 cycle (11.42 %). Results from genomic analysis together with differences in phenotypic features and chemotaxonomic analysis support the proposal of strain SAICEUPSMT as the type strain of a novel species for which the name Pseu-domonas mercuritolerans sp. nov is proposed. The absence of virulence genes and transmissible resistance mechanisms reveals its safety for agronomic uses, under mercury stress conditions.